基于ME的齿轮铣刀CAD/CAM - 包耳; 康晶; 邵强 (Jixie chuandong)
CAD/CAM of form milling cutter of gear based on Manufacture Engineer（ME） improves the precision of cutter edge curve and manufactured gears, and prolongs the life of cutter. In the Milling cutter CAD/CAM, the ME software is used to establish 3-D modling of cutter, process simulation of cutter manufacturing and program automatically for CNC cutter grinder. The methods of edge curve design, tool-path calculation and manufacture processing of cutter on CNC cutter grinder are discussed. Machining examination indicates that precision of manufactured gear tooth increases by 2～3 levels by eliminating the error of cutter edge curve and profile modeling system, and the life of cutter increases by 2～4 times.